Factors influencing same-day discharge after minimally invasive hysterectomy for malignant and non-malignant gynecological diseases: a systematic review and meta-analysis - Liu, Jia; Chen, Yali; Tan, Xin; Chen, Hengxi (Frontiers in Oncology, 2024)
Objective: To explore the factors influencing the successful implementation of same-day discharge in patients undergoing minimally invasive hysterectomy for malignant and non-malignant gynecological diseases. Method: We searched PubMed, Embase, Cochrane Central Register of Controlled Trials, International Clinical Trials Registry Platform, and Clinical Trials.gov from inception to May 23, 2023. We included case-control and cohort studies published in English reporting same-day discharge factors in patients undergoing minimally invasive hysterectomy for malignant and non-malignant gynecological diseases. STATA 16.0 was used for the meta-analysis. Risk factors were assessed using odds ratios (OR) (relative risk (RR)/hazard ratios (HR)) with 95% confidence intervals (CI), and logistic regression determined the same-day discharge rate (%). Results: We analyzed 29 studies with 218192 patients scheduled for or meeting same-day discharge criteria. The pooled rates were 50% (95% CI 0.46-0.55), and were similar for malignant and non-malignant gynecological diseases (48% and 47%, respectively). In terms of basic characteristics, an increase in age (OR: 1.03; 95% CI: 1.01–1.05), BMI (OR: 1.02; 95% CI: 1.01–1.03), and comorbidities including diabetes and lung disease were risk factors affecting SDD, while previous abdominal surgery history (OR: 1.54; 95% CI: 0.93–2.55) and hypertension (OR: 1.53; 95% CI: 0.80–2.93) appeared not to affect SDD. In terms of surgical characteristics, radical hysterectomy (OR: 3.46; 95% CI: 1.90–6.29), surgery starting after 14:00 (OR: 4.07; 95% CI: 1.36–12.17), longer surgical time (OR: 1.03; 95% CI: 1.01–1.06), intraoperative complications (OR: 4.68; 95% CI: 1.78–12.27), postoperative complications (OR: 3.97; 95% CI: 1.68–9.39), and surgeon preference (OR: 4.47; 95% CI: 2.08–9.60) were identiﬁed as risk factors. However, robotic surgery (OR: 0.44; 95% CI: 0.14–1.42) and intraoperative blood loss (OR: 1.16; 95% CI: 0.98–1.38) did not affect same-day discharge. Conclusions: An increase in age, body mass index, and distance to home; certain comorbidities (e.g., diabetes, lung disease), radical hysterectomy, surgery starting after 14:00, longer surgical time, operative complications, and surgeon preference were risk factors preventing same-day discharge. Same-day discharge rates were similar between malignant and non-malignant gynecological diseases. The surgery start time and body mass index have a greater impact on same-day discharge for malignant diseases than non-malignant diseases.